(untitled) (Fiep Bulletin - online, 2012)
The aim of this study was to evaluate the standard motor using the over head mode in adults with autism and identify effective instructional procedures to facilitate acquisition, retention and transfer of manipulative skill for the variability of motor action. It was a case study. The sample consisted of four adults with clinical diagnosis of autism (CID F.84.0) chronological age between 19 and 25; standard mature motor of walking directed; systematic frequency, at least 18 months, in the Extension in Motor Activity Project to children and teenagers with autism (PREMAUT) from the physical education course of Federal University of Alagoas in Maceió. Materials and methods: documentary analysis, interviews and the application of motor tests based on postulates Gallahue and Ozmun (2003). The results, pre-test showed that subjects (A, B and C) are at an initial stage in the task of low complexity of the standard motor for over head. In tasks of medium and high complexity were not properly performed by the group. Subject (D) in the elementary stage three levels of complexity. The program Motor Skills Training (HAT) allowed the subject: to know the space and feature freely available on the THA (adaptive phase) circuits and experience structured and semi-structured and non-locomotor variability of plans and teaching resources (training phase). The post-test identified: mature stage in the task of low complexity and elementary stage in the task of medium and high complexity (Subject A). Elementary training for low, medium and high complexity tasks (Subject B). Mature stage for tasks of low and medium complexity and initial high complexity tasks (Subject C). Mature stage for low, medium and high complexity tasks (Subject D). It is concluded that the use of structured circuits without variability of the task and learning resources, is effective in the acquisition, retention and transfer skills in over head mode.